Citykern und City - Niemeier, Georg (ERDKUNDE, 1996)
Various terms, such as urban core, old town, central area etc., are first of all defined. Then the City is investigated in terms of combinations of characteristics, above all in terms of socio-economic functions and their spatial arrangement with a division into city-core and city-periphery. Possibilities of delimitation areal calculation are also investigated with examples from West Germany and abroad. Various methods of defining the City which can be used in combination are discussed (calculations from statistical enumeration districts, mapping of building functions, employment centres and workplaces etc.) and partially demonstrated by examples for which investigations and cartographic work in Braunschweig form the basis. There is no generally-applicable catalogue of facilities found exclusively in the City, not even of strongly City-tied specialist shops, because the type and number of these in western industrial society are dependent on the population of a town and its surrounding area and on the needs of its in habitants, i. e. on the economic and social structure of the town and its surrounding area. One does, however, find a massing of facilities, of private and public service enterprises, which find their optimal location in a City. The precondition for development of a City is, however, not necessarily an important central place function; a City can also be generated by the internal requirements of a town (e. g. Gelsenkirchen, a mining and heavy-industrial town). Because of the inhomogeneity of building uses and functions and because of the often gradual transition of the City into an urban core area without pronounced City functions, clear boundaries for a City can only be fixed by the use of conventions (such as landvalue boundary or through indices in the sense of the north American Central Business District [CBD]). The urban core of smaller towns, but also the City-core of large and million-cities, often consists of only one street axis with short branches, designated here as the 'City artery'. The area of the City (or CBD) mostly covers less than 2 km²; indeed mostly less than 1 km² (with many exceptions, especially in cities of world rank such as Chicago). The CBD's of 14 north American and Australian large towns have a mean size of 0,52 km². Statistical enumeration districts are too large to act as data units for the recognition of socio-economic urban structures and therefore lose sight of important structural characteristics. House to house mapping or the formation of significantly smaller enumeration districts than are at present available appear urgently needed. Indeed, one should not shrink from sub-dividing building blocks, since electronic data processing can quickly provide maps showing an exacter definition, division and delimitation of Cities. (Indices such as inhabitants per hectare, employment centres and workplaces in a threefold division, day and night population and functional building types would then be quite adequate). Various problems of the City, which are currently important for the functional efficiency and competitiveness of a town e. g. contraction processes, shortage of parking facilities and other traffic problems, lack of activity after business hours etc., are discussed and some attempts and recommendations for their solution outlined.